The impact of green marketing on the consumers' intention to buy green products in the context of the Green Deal - Lavinia Denisia Cuc; Corina Pelău; Silviu-Gabriel Szentesi; Grigorie Sanda (Amfiteatru Economic Journal, 2022)
To counteract the negative effects of environmental degradation and climate change, in the European Union, a set of measures and policies has been developed under the name of the Green Deal, which aims to develop a competitive and resource-efficient economy. For these measures to be sustainable, it is important to have green marketing to promote green consumption and an environmentally friendly attitude. The aim of this paper is to determine the empirical relation between the instruments of green marketing and the ecological behavior and attitude of consumers and the impact it has on the future intention to buy green products. The results of a structural equation model show that although product and communication policies are more closely associated with green marketing, digital tools have the greatest impact on green behavior. Their easy way of use has side effects on ecological behavior. A mediation model empirically demonstrates that the willingness to buy green products, the environmentally oriented lifestyle, and the willingness to pay more for green products mediate the relationship between the current ecological behavior and the intention to buy green products in the future.
Keywords: M21; M31; 330; Green marketing; green products; environmentally friendly behavior; Green Deal; European Union